Tyrosine hydroxylase deficiency causes progressive encephalopathy and dopa-nonresponsive dystonia - Hoffmann, Georg F.; Assmann, Birgit; Bräutigam, Christa; Dionisi‐Vici, Carlo; Häussler, Martin; Klerk, Johannes B. C. De; Naumann, Markus; Steenbergen‐Spanjers, Gerry C. H.; Strassburg, Hans-Michael; Wevers, Ron A. (Annals of neurology, 2003)
Tyrosine hydroxylase (TH) is the key enzyme in the biosynthesis of the catecholamines dopamine, epinephrine, and norepinephrine. Recessively inherited deficiency of TH was recently identified and incorporated into recent concepts of genetic dystonias as the cause of recessive Dopa-responsive dystonia or Segawa's syndrome in analogy to dominantly inherited GTP cyclohydrolase I deficiency. We report four patients with TH deficiency and two with GTP cyclohydrolase I deficiency. Patients with TH deficiency suffer from progressive infantile encephalopathy dominated by motor retardation similar to a primary neuromuscular disorder, fluctuating extrapyramidal, and ocular and vegetative symptoms. Intellectual functions are mostly compromised. Prenatally disturbed brain development and postnatal growth failure were observed. Treatment with levodopa ameliorates but usually does not normalize symptoms. Compared with patients with dominantly inherited GTP cyclohydrolase I deficiency, catecholaminergic neurotransmission is severely and constantly impaired in TH deficiency. In most patients, this results not in predominating dystonia, a largely nondegenerative condition, but in a progressive often lethal neurometabolic disorder, which can be improved but not cured by L-dopa. Investigations of neurotransmitter defects by specific cerebrospinal fluid determinations should be included in the diagnostic evaluation of children with progressive infantile encephalopathy. Ann Neurol 2003;54 (suppl 6):S56-S65
Gesehen am 22.12.2020